The Problematic Legalizing of the Husband’s Will to Divorce Between Authenticity and Modernity : A Comparative Study - HMIDA, Imad; MARMOUNE, Moussa (Journal of Human Sciences, 2020)
The issue of divorce by the sole will of man is one of the most controversial issues between the traditional and innovative Islamic jurisprudence and also the Modernist doctrine. To this prin-ciple, the Algerian family law like other Arabic personal status laws regulated the dissolution of marriage according to the divorce system in Islamic law. but however, this issue witnessed objections in second half of Twentieth century, Led by two different currents in terms of refere-nces, although they share the same objectives and propose to limit the right of man to divorce. so, we will stand and discuss through this research paper the objections, doctrinal and personal argu-ments of a part of contemporary jurisprud-ence, and to the arguments of the modernist doctrine which adopted the references of feminist move-ment and the principles of the international hum-an rights law. also we will devise the pos-ition of the Algerian legislator, and Arabic legislations who has restricted the right to divorce.